(3Sde GdSeGA hGdBaGb aj GdQHY GdeLjHs - (3Ydj Hf aVd Gddg Hf eMeO GdeQYTj GdTGaYjs
(3ChdgG (B:s
(3jGef bOQ GddjGdi hGdCjGe hHYO , ajbhd deG cGf eYQaI GdbHdI hGdejbGJ , ehbhaI Ydi GdYed HGdCSWQdGH hHeLjH QHY GdOGFQI hGdebfWQGJ , CdaJ QSGdI ai GdeLjH eTJedI Ydi ebOeI hNeSI hYTQjf ef GdCHhGH s
(3BNQgG (B:s
(3Ke ffbd GdNjW Edi LjH GdJeGe , aEf de jJaGhJ ai GdbWY agh UMjM bO Je JMQjQ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3CJe GdeDda JCdjagG SfI (B1140 (3g`s
(3cJHJ Hbde ajg edGeM GdNW GdaGQSis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B166 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B765s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs